Asset Management, Optimization of Asset Use, and its Effect on Local Own-Source Revenue - Linuhung, Tiara Setra; Mediawati, Elis (IJBLE Scientific Publications Community Inc., 2023)
Assets are one of the tools to generate revenue for a country. Given the important role of assets, this study aims to comprehensively determine the effect of asset management and asset optimization on PAD. The method used is literature study with descriptive analysis. The research results from 13 regions, 6 of which show that asset management has an effect on PAD, 2 regions state that asset management has no effect on PAD, 2 regions prove that asset optimization has an effect on PAD, and 3 regions state that asset management has no effect on PAD. The author can also conclude that asset management/management and asset optimization are closely related and affect each other.